Role of perioperative nutritional status and enteral nutrition in predicting and preventing post-operative complications in patients with Crohn’s disease - Jiang, Tianyu; Jiang, Yongmei; Jin, Qianwen; Xu, Shining; Fingerhut, Abraham; Shi, Yongmei; Zheng, Minhua; He, Zirui (Frontiers in Nutrition, 2023)
(1) Background: Perioperative immune-nutritional status is correlated with postoperative outcomes. This study aimed to evaluate whether pre-operative nutritional status could predict postoperative complications in patients with Crohn’s disease (CD) and whether preoperative enteral nutrition (EN) can prevent postoperative complications. (2) Method: This retrospective cohort study analyzed the electronic health records of 173 patients diagnosed with CD in Ruijin Hospital, Shanghai, China, between Aug 2015 and May 2021: 122 patients had preoperative nutritional support while 51 patients underwent surgery without preoperative nutritional support. The preoperative nutritional status, disease activity index, disease-related data, frequency of multiple surgery, operative data, and postoperative characters in each group were compared to determine whether the nutritional support and status could significantly affect postoperative outcome. One-to-one propensity score matching (PSM) was performed to limit demographic inequalities between the two groups. (3) Results: After PSM, no statistically significant differences were found in preoperative patient basic characteristics between the two groups of 47 patients (98 patients in all) included in this study. Overall, 21 patients developed 26 postoperative complications. In terms of preoperative nutritional status, the level of serum albumin, prealbumin, and hemoglobin in the nutrition group were statistically higher than that in the control group. We also observed a statistically significant decrease in postoperative complications, need for emergency surgery, and staged operations, while the rate of laparoscopic surgery was higher in the nutrition group compared to the non-nutritional group. Postoperative complications were related to preoperative nutritional condition, which indicated that EN may improve the nutritional status and reduced the rate of postoperative complications. (4) Conclusion: Preoperative nutritional status is correlated with postoperative outcomes while EN plays a positive role in preventing the postoperative complications. EN is useful for improving the preoperative nutritional status and reducing the postoperative adverse events for CD patients undergoing surgery.